Modelo de simulação de eventos discretos aplicado ao planejamento e operação de rodovias - Paula, Marcelo Barros de (2006)
This study proposes a methodology to classify highway network flow and service levels based on a combination of the basis of the Highway Capacity Manual HCM and Simulation. According to these past studies the model proposed by this study lies into the mesoscopic traffic simulation where the model describes individuals vehicles but not their interactions. This is an intermediary level between microscopic and macroscopic traffic simulation because, although the vehicles are represented individually and theirs speeds are individually maintained, their behaviour is not modeled in detail.